"A Life Lived": Collective Memory and White Racial Framing in Digital Opioid Overdose Obituaries. (December 2020) - Revier, Kevin
With a rise in overdose deaths in the United States, opioid awareness has come in a variety of ways. One of these, as reporters suggest, is obituary writing. Obituaries are considered in news media as offering "brutally frank" depictions of addiction that "chronicle the toll of heroin." Moreover, obituary sharing by parents and loved ones has increasingly taken place on digital platforms, memorial websites expanding the visibility of overdose death while facilitating the building of virtual grief communities. Not solely commemorating individual loss, obituaries thus contain symbolic power—they reflect dominant social values and shape collective memory. As such, overdose obituaries inform how opioid crisis is framed, represented, and addressed. From a qualitative content analysis of 533 opioid-related U.S. obituaries published onLegacy.com andObitTree.com, I find that while obituaries reduce stigma associated with drug use, addiction, and overdose, they primarily tell white tales of addiction. In affording a white racial framing of drug addiction, obituary writing corresponds with a larger whitewashing of the opioid crisis while implicitly constructing symbolic boundaries between those memorialized, who are predominantly white and middle-class, and those who are deemed as raced and classed Others. Such storytelling, particularly when popularized in news media and made visible on digital platforms, contributes to ongoing systemic inequality in the prevailing drug war.